RETRACTED: Les Effets De L’offre De Credit Sur Les Fluctuations Economiques Dans La Cemac - Mouakassa, Prudence Love Angèle; Mantsie, Rufin Willy (European Scientific Journal, ESJ, 2019)
Based on a complaint received from a third party on 16.08.2023, the ESJ Ethics Committee has retracted the paper Mouakassa, P. L. A., & Mantsie, R. W. (2019). Les Effets De L’offre De Credit Sur Les Fluctuations Economiques Dans La Cemac. European Scientific Journal, ESJ, 15(34), 316. https://doi.org/10.19044/esj.2019.v15n34p316 published in the European Scientific Journal on 31.12.2019. The complaint alleged that the authors of the ESJ paper have failed to properly acknowledge the sources of the content they used. Furthermore, inconsistencies and potential errors were noticed that cast doubt on the thoroughness of the research and referencing. Many references cited in the content are missing from the list of references. This case was reviewed by the ESJ Ethics Committee and the authors of the disputed paper were immediately contacted. Although not a direct form of plagiarism the ESJ Ethics Committee has accepted the allegations and contacted the authors to correct the errors. The corresponding author responded that he forwarded this to the co-author for correction. The corrections were not received within the timeframe (more than 2 months). Therefore the ESJ ESJ Ethics Committee suggested retraction of the paper by issuing a retraction notice. The ESJ Ethics Committee concluded that the paper will be retracted due to numerous improper citations, errors in the referencing, and other mistakes in the content.